A retrospective analysis to assess the reasons for the failure of dental implants - Greeshma Vani Yarramsetty; Bindhu Madhavi Singiri; K R Vijay; V C Balaji; Kaki Anusha; Roger P Thota (Wolters Kluwer Medknow Publications, 2023)
Background: To assess the reasons for dental implant failures. Materials and Methods: A total of 100 implants were studied in 80 subjects. The radiographic investigations were performed to assess the record length of implant and diameter of implant. Risk factors, such as habit of smoking, history of diabetes, and hypertension, were recorded. The data were collected and assessed using Statistical Package for the Social Sciences (SPSS) software. The one-way analysis of variance (ANOVA) test was used to assess the failure rate in dental implants. A P-value less than 0.05 was considered statistically significant. Results: A total of 100 dental implants were included. The maximum dental implant failure was seen with a diameter <3.75 mm (30%) followed by 3.75-4.5 mm (16%) and >4.5 mm (6.15%). The difference was found to be significant (P < 0.05). Conclusion: Dental implant failure was high in dental implants with <3.75 mm diameter, dental implants with a length <10.0 mm, and among smokers.